ANALYSIS OF WORKING POSTURE USING THE REBA METHOD AND ERGONOMICS APPROACH TO EMPLOYEES OF THE POLYPROPYLENE PRODUCTION DIVISION AT PT HARAPAN SEJAHTERA KARYA UTAMA SIDOARJO - Jasur, Jasur; Suryadi, Akmal (Journal of Industrial Engineering Management, 2024)
PT Harapan Sejahtera Karya Utama is a company engaged in the plastic industry, especially polypropylene. This company has been distributed to companies in East Java. Four workstations still do not apply ergonomic work postures in the production process. This research aims to determine the action level value of the REBA score and design an ergonomic work posture. From the research that has been done, it was found from the Nordic Body Map (NBM) questionnaire that 58% of workers have pain in the back, and 47% have pain in the waist. Related to the REBA scoring results, in the process of checking raw materials, the process of cutting materials, and packaging, the REBA score of 5 was obtained, which is a medium risk with an action level of 2. the process of transfer materials obtains the REBA score of 11, which is a very high-risk with an action level value of 4. Based on the REBA score, a proposal was made to improve the working posture of workers in the polypropylene production division, the process of checking raw materials, the process of cutting materials and packaging, and obtained a REBA score of 2 out of 5, where this value is better than the initial work posture score. For the material transfer process, the REBA score is 3 out of 11, where this value is better than the initial work posture score. Related to this, the company should pay attention to the safety and health of employees when doing a job, such as the optimal work posture at work.